RANCANG BANGUN CHARGER OTOMATIS PENGONTROL DAYA DAN WAKTU BERBASIS ARDUINO UNO - Mohammad Wahyu Habibulloh; Kurnia Paranita Kartika (Antivirus : Jurnal Ilmiah Teknik Informatika, 2019)
This final project discusses the design and manufacture of an arduino UNO-based power and time controller automatic charger. On an ordinary charger still does not have a mechanism to cut off the electricity that goes into the charger completely, so researchers have an idea to develop an automatic charger to increase the efficiency of battery charging and to increase the battery life of smartphones. This tool is used to control the charging of a smartphone on the basis of a battery that is used is a capacity of 4100mAH, with the charger used is the Xiaomi 0.35A charger. the remaining percentage of the battery is controlled by using a keypad, the charger will charge the battery in accordance with the time set on each keypad button. The amount of time the battery is charged is displayed on the LCD. When the charging time has finished the relay that is connected to the charger outlet will disconnect the electricity that leads to the charger to stop the charging process and the buzzer will light up as the charging indicator has finished and the LCD will display the words "charging has finished". Through testing conducted by the researchers themselves and testing the device to the user charging the battery using an arduino UNO-based automatic charger, the results are that the automatic charger can charge the battery with accuracy reaching 98% to 99% of the battery capacity and can stop charging according to the specified time. Suggestions that can be given by the authors for further research are the use of a custom keypad that is equipped with information on each key to facilitate the user, the use of RTC to calculate battery charging time, as well as the development of a backup power source in the event of a power outage.